The Role of the Four Pillars in Heart Failure with Reduced Ejection Fraction (HFrEF) and Heart Failure with Preserved Ejection Fraction (HFpEF): How Different? - Dentino Wili Mahendra (Al Makki Publisher, 2025)
Heart failure (HF) remains a major clinical challenge, with two main phenotypes: heart failure with reduced ejection fraction (HFrEF) and heart failure with preserved ejection fraction (HFpEF). These conditions exhibit distinct pathophysiology, clinical manifestations, and therapeutic responses, requiring distinct management approaches. The four pillars of HFrEF therapy—renin-angiotensin system (RAS) inhibitors, β-blockers, mineralocorticoid receptor antagonists (MRAs), and sodium-glucose cotransporter-2 (SGLT2) inhibitors—have been shown to reduce mortality and morbidity. In contrast, HFpEF management focuses more on risk factor control and symptom-based therapy, with SGLT2 inhibitors being the only treatment that has shown significant clinical benefit. This literature review aims to evaluate the different roles of the four pillars of therapy in both phenotypes of heart failure and their implications for clinical practice. Although HFrEF treatment has made significant progress with strong clinical trial evidence, HFpEF management still requires further exploration to identify more effective strategies. Therefore, a deeper understanding of each phenotype's pathophysiology and therapeutic response is essential to improve patient outcomes and optimize heart failure management.